Assessment of the Hybrid Entrepreneurial Interest Instrument Utilizing Rasch Model Analysis - Hastini, Lasti Yossi; Rivai, Harif Amali; Pujani, Vera; Rahman, Hafiz (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
Usability of the Rasch Model: A Study to Develop a Valid and Reliable Measure of Hybrid Entrepreneurial Interest It explored the cultural bias that exists between Minangkabau and non-Minangkabau people. 108 people had completed the three measures, and their respective data were subjected to tests of reliability, validity, and DIF. Results showed that the instrument has good reliability, evidenced by high item and person reliability coefficients and a large separation index. Most items were fitted via the Rasch Model, while some showed small signs of bias. The DIF analysis showed noteworthy cultural differences on several items, most prominently Interest 4, which presented a significant DIF difference. These results suggest a disparity in economic entity perception between the Minangkabau respondents, who grew up with cultural values promoting big capital entrepreneurship with possible aspirations to achieve economic stability, and the non-Minangkabau respondents. The findings highlight the need of considering cultural contexts when developing measures of risk preference in relationship to entrepreneurship. The tool has worked well, but it still needs refinement to be more culturally neutral and widely applicable. This study contributes to entrepreneurship theory by expanding our understanding of culturally responsive entrepreneurship and offers practical recommendations to encourage culturally responsive entrepreneurial efforts.